Produção diferencial de óxido nítrico e intermediários reativos de oxigênio por neutrófilos de camundongos susceptíveis e resistentes à infecção por Leishmania major - Myrian Morato Duarte (2008)
In this study we investigated the interaction between Leishmania major promastigotes and neutrophils of two mouse strains, BALB/c and C57BL/6, the prototype hosts for susceptibility and resistance to L. major infection. We showed intrinsic differences between neutrophils of these two mouse strains in the nitric oxide (NO) production, reflected in nitric oxide syntase (iNOS) expression. C57BL/6 neutrophils produced more NO after IFN-γ and LPS exposure than BALB/c cells. L. major promastigotes were able to reduce NO production and iNOS expression, in both mouse strains. We demonstrated that oxygen radicals production, another microbicidal mechanism of neutrophils, differed between cells of the two mouse strains. Neutrophils from BALB/c mouse produced more oxygens radicals than C57BL/6 cells after PMA stimulation. The p40phox and p47phox expression was distinct in neutrophils from those two strains. The oxygen radicals production is inhibited by interaction with L. major promastigotes.